Effectiveness of Using Spent Bleaching Earth Stabilized Using Seashells on Concrete Compressive Strength - Garcya, Muhammad Gala; R, Juli Ardita Pribadi; Rahman, Boby; Maulana, Ryan (Politeknik Negeri Bengkalis, 2024)
Bleaching Earth is a material used to refine palm oil to make it brighter in color as we currently consume.However, due to this, the accumulation of Bleaching Earth is increasingly uncontrolled and continues to accumulate.Previously, this research had been carried out but had not found a major impact on concrete durability. Especially incoastal areas which are often exposed to high chloride ions and have the potential to damage concrete. This research aimsto create a material that can modify the properties of concrete to have better durability by modifying Spent BleachingEarth using seashells. This research uses a cylinder measuring 150 x 300 mm with a various admixture. In this research, 3(three) stabilization fraction models were tried, namely Fraction A with 60% SBE and 40% Seashells, fraction B with50% SBE and 50% Seashells, and fraction C with 40% SBE and 60% Seashells. The research showed that fraction Bshowed compressive strength reaching 22,85 MPa and Fraction C showed compressive strength up to 29,44 MPa at 28days. Meanwhile, Fraction A experienced a decrease in compressive strength, reaching only 20,64 MPa compared tonormal concrete of 21,90 MPa at 28 days. This could be caused by many things, so further research is needed regardingthe stabilization of these two materials. Based on the research, it can be concluded that Fraction C can be arecommendation because it has higher strength than other fractions and needs to be tested in aggressive environments,especially in coastal areas